An overview of the public relations function - Bowen, Shannon A.; Rawlins, Brad; Martin, Thomas R. (Public relations collection, 2010)
This book provides an executive review of the field of public relations with a focus on what managers need to know in order to master the function quickly and effectively. Throughout the text, we integrate the academic with the professional by asking, how can an executive use this knowledge to make the most of the public relations function, department, and initiatives in order to help their whole organization be successful?"--Abstract from book.